Potentially Overlooked Risk for Neuropsychiatric Symptoms in Children: Montelukast Treatment - Tunca, Seda; Yilmaz, Ozge; Ocalan, Merve; Arga, Mustafa; Cavkaytar, Ozlem; Ozceker, Deniz; Yuksel, Hasan (Wiley, 2025)
Background Montelukast is a leukotriene receptor antagonist commonly used in allergic diseases. In this study, we investigated the frequency, severity and risk factors for neuropsychiatric side effects and sleep disorders associated with montelukast in children. Method Children aged 6 months to 17 years prescribed montelukast for allergic rhinitis or asthma at 31 Paediatric Allergy and Immunology centres were enrolled in this cohort study. At enrollment, sociodemographic characteristics, prior diagnoses of neuropsychiatric diseases or sleep disorders, and indications for montelukast treatment were recorded, and the primary caregivers completed a baseline questionnaire about neuropsychiatric symptoms (insomnia, nightmares and depressed mood) of their children. All participants were followed up for 1 month, and a post-treatment follow-up questionnaire on neuropsychiatric symptoms was completed at the end of this period. Moreover, caregivers were instructed to contact the clinic if neuropsychiatric side effects or sleep disorders were observed during this period. Results Total of 1163 children were enrolled. There was a significant increase in the frequency of insomnia, nightmares, night terrors, drowsiness, behavioural problems, irritability, depressive mood, agitation, anxiety, hyperactivity, learning difficulties and headache during the 1 month period after montelukast treatment compared to the previous 1 month (p < 0.001 for all). Overall, caregiver reports of neuropsychiatric symptoms in children increased from 172 (14.8%) to 399 (34.3%) after 1 month of montelukast treatment (p < 0.001). Conclusions Montelukast treatment increases the risk of neuropsychiatric symptoms and sleep disorders in children with allergic diseases, especially if there is concomitant use of antihistamines.
Keywords: allergy; antihistamine; asthma; montelukast treatment; neuropsychiatric symptoms